Adaption of Theoretical Adsorption Model on Coal: Physical Structure - Guodai, Wu; Linhua, Pan; Bingxiang, Huang; Jinhua, Luan; Ye, Zhang; Ruigang, Zhang; Zheng, Sun (Frontiers in Earth Science, 2021)
With the motivation to investigate the role of coal physical structure on the adsorption performance of coal reservoir, 18 different types of coal samples with different coal structures were collected from six coal profiles of four production mines located at China. The adsorption characteristics of CH4 on coal samples with different coal structures were examined, and then experimental results were fitted and analyzed by the Langmuir model and the adsorption potential model (D-R and D-A). The prominent factors in terms of adsorption capacity of coal with different coal structures and its adaptability to the model were discussed. Results indicate the following: a) under the condition of a similar coal rank, the adsorption performance of coal is governed by coal rock composition and adsorption heat, the effect of structural deformation on the adsorption performance of coal is not obvious; b) the Langmuir model has a certain adaptability to coal samples with different coal structures, while the D-R model is evidently not suitable to describe coal samples with scaly coal, part of broken coal with small vitrinite content; c) the D-A model has a high adaptability to coal samples with various coal structure types, and the stronger the coal deformation is, the higher the accuracy is.